Evaluation of APRI and FIB-4 indices in early and late-onset preeclampsia - Vanlı Tonyalı, Nazan; Karabay, Gülşan; Aktemur, Gizem; Tokgöz Çakır, Betül; Şeyhanlı, Zeynep; Çetin, Sevinç; Çağlar, Ali Turhan (The European Research Journal, 2025)
Objectives: This study aimed to evaluate the relationships between maternal and neonatal outcomes and the Fibrosis-4 Index (FIB-4) and Aspartate Aminotransferase-to-Platelet Ratio Index (APRI) in healthy pregnancies, late-onset preeclampsia (LOP), and early-onset preeclampsia (EOP). Methods: A retrospective study was conducted on 239 pregnant women diagnosed with EOP (n=62), LOP (n=56), and healthy pregnancies (n=121) at Etlik City Hospital. Maternal and neonatal outcomes, as well as APRI, and FIB-4 scores were compared. Statistical analyses included ANOVA, chi-square tests, and ROC curve analysis. Results: EOP was associated with lower gestational age at birth, lower fetal birth weight, and higher NICU admission rates compared to LOP and control groups. APRI scores were significantly elevated in LOP compared to controls (P=0.012). FIB-4 scores were significantly higher in LOP than controls (P=0.005). ROC analysis showed modest predictive power for APRI (AUC=0.614) and FIB-4 (AUC=0.617) in distinguishing LOP from controls. The best cut-off values for APRI and FIB-4 were 0.2347 and 0.65, respectively. Conclusions: Elevated APRI and FIB-4 scores in LOP suggest their potential roles as complementary markers in preeclampsia management. However, their moderate predictive performance indicates the need for further studies.